The Impact of the Najiz System on the Services Provided by the Ministry of Justice in Saudi Arabia - Mr. Azzam Naif Almutairi; Prof. Fahad T. Bin Muhaya (International Journal on Orange Technologies, 2023)
This research paper aimed to evaluate the effectiveness of the Najiz system, an electronic platform designed to facilitate the processing of legal cases and property Transfers and identify areas for improvement in the Saudi judicial system. The study aimed to provide insights into the impact of digital transformation on the Ministry of Justice and the effectiveness of the Najiz system in delivering equitable justice promptly to Saudi nationals. The study employed a mixed-methods research approach that utilized both qualitative and quantitative research methods. The survey questionnaire used in the study collected data from a diverse range of respondents, including lawyers, judges, and citizens with experience using the Najiz system. the study identified several areas of improvement for the Najiz system, including expanding cloud computing technology, improving user skills, and continuously evaluating and improving the system by seeking feedback from users. The study's recommendations have significant implications for the digitization of the Saudi judicial system and the government's commitment to achieving equitable justice delivered promptly to all Saudi nationals. Overall, this research paper provides valuable insights into the effectiveness of the Najiz system and the potential of digital transformation in delivering equitable justice promptly to Saudi nationals. The study's findings and recommendations provide a basis for future research and contribute to ongoing efforts to enhance the effectiveness of the Saudi judicial system.